2016
DOI: 10.1007/978-3-319-46750-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Correctness of Model Transformations While Remaining Decidable

Abstract: Abstract. This paper is concerned with the interplay of the expressiveness of model and graph transformation languages, of assertion formalisms making correctness statements about transformations, and the decidability of the resulting verication problems. We put a particular focus on transformations arising in graph-based knowledge bases and model-driven engineering. We then identify requirements that should be satised by logics dedicated to reasoning about model transformations, and investigate two promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In [24], the authors presented another survey of approaches for verifying model transformations. In [7], the authors identified the requirements that should be satisfied by logics used for reasoning about model transformations. They investigated decidable fragments of first-order logic.…”
Section: Related Workmentioning
confidence: 99%
“…In [24], the authors presented another survey of approaches for verifying model transformations. In [7], the authors identified the requirements that should be satisfied by logics used for reasoning about model transformations. They investigated decidable fragments of first-order logic.…”
Section: Related Workmentioning
confidence: 99%
“…We hope to manage to give readers an idea of the logical foundation of our method without spending too much time and space on information that would not be relevant to most end-users. Readers interested in a more formal and in-depth description can find it in Brenas et al (2016aBrenas et al ( , 2018b.…”
Section: Logic Graph Rewriting and Verificationmentioning
confidence: 99%
“…This process is achieved by two functions: the weakest-precondition wp ( s, Q ) and the verification condition vc ( s, Q ) for a strategy s and a post-condition Q . More details can be found in Brenas et al ( 2016a ). The definitions of these functions are given in Figures 2 , 3 , respectively.…”
Section: Logic Graph Rewriting and Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…These features can often lead to undecidability of both model checking and satisfiability of such logics, see [5], [6]. -Other relevant references to mention here include [10] and [16].…”
Section: Introductionmentioning
confidence: 99%